Looped In Lupus-An Unusual Manifestation - Mohammed Shanil P,; Farsana Jasmin K, (International Journal of Scientific Research in Science and Technology, 2024)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disorder that can involve the central nervous system (CNS) in 40-70% of cases. Neuropsychiatric SLE presenting as parkinsonism is rare. We present a case of a 39-year-old woman who initially presented with polyarthritis and fever, followed by difficulty walking and speech impairment. Examination revealed an expressionless face, low-volume speech, resting tremors, and limb rigidity without cerebellar or sensory deficits. Investigations revealed ANA positivity, elevated anti-dsDNA and anti-Sm antibodies, proteinuria, and multiple brain infarcts. The patient was treated with Methylprednisolone, Levodopa, and Hydroxychloroquine, showing clinical improvement. Physicians should suspect SLE in patients with parkinsonism and polyarthralgia, as vasculopathy due to impaired thalamostriate arteries may contribute to parkinsonism.
Keywords: Systemic Lupus Erythematosus; SLE; CNS involvement; Neuropsychiatric SLE; Parkinsonism